American genesis the evolution controversies from Scopes to creation science - Moran, Jeffrey P. (New York Oxford University Press, 2012)
The question of teaching evolution in public schools is a continuing and frequently heated political issue in America. From Tennessee's Scopes Trial in 1925 to recent battles that have erupted in Louisiana, Kansas, Ohio, and countless other localities, the critics and supporters of evolution have fought nonstop over the role of science and religion in American public life. This book explores the ways in which the evolution debate has reverberated beyond the confines of state legislatures and courthouses.
Keywords: Electronic books; Evolution (Biology) -- Study and teaching -- United States -- History; Evolution (Biology) -- United States -- Religious aspects -- Christianity -- History; Creationism -- United States -- History